(untitled) (Journal of Student Affairs in Africa, 2021)
Most first-year university students experience serious academic and adjustment challenges, which remain undetected until it is too late to provide meaningful intervention. Universities are therefore developing academic support systems that can assist in identifying students who experience learning challenges early on, and provide quality first-year experiences that ensure that first-year students adapt, engage and succeed at the university. Such student academic support systems should provide resources that detect risk factors as early as possible. This study explores the support provided by the Retention Officers (ROs) in assisting first-year students to overcome disengagement issues at the Cape Peninsula University of Technology in Cape Town, South Africa. Modelled on Tronto’s (2010) Theory of Ethics of Care, the design of the First-Year Experience project is underpinned by the value of inclusion and care for first-year students in higher education. This practitioner-based paper draws on the experiences of ROs in monitoring first-year students’ disengagement in a science faculty at the Cape Peninsula University of Technology. Data extracted through interviews and written reports by ROs formed the basis for a qualitative interpretation of ROs’ experiences dealing with firstyear students’ disengagement. This paper therefore highlights the importance of mediating between discipline-based support and generic psycho-social support through the involvement of ROs to enhance student engagement.